PENINGKATAN WAWASAN DAN MOTIVASI KEWIRAUSAHAAN BAGI SISWA SMK NUSA BHAKTI PENGASINAN SAWANGAN DEPOK - Sairin Sairin; Tarwijo Tarwijo; Fathorrahman Fathorrahman; Suryadi Marthadinata; Suworo Suworo (LPPM Universitas Pamulang, 2020)
This Community Service is titled Improving Insights and Motivation of Entrepreneurship for Students of SMK Nusa Bhakti, Pengasinan, Sawangan, Depok. The purpose of community service activities is to provide counseling and lectures and questions and answers on the importance of entrepreneurship and motivation to students in building strong human resources in preparation for competing in the world of work for students of Vocational High School (SMK) Nusa Bhakti, Pengasinan, Sawangan, Depok. This service activity method takes place from September to December 2019 and consists of three stages of activity. The first stage is the preparation phase by conducting a survey of partner locations, participant activities and preparation of material, the second stage is the implementation which includes giving lecture training material on motivation and entrepreneurship, making a business plan, calculating the cost of goods sold, and others. The third stage is the interalai evaluation to find out how much in the participants' understanding of the material provided, mentoring the trainees independently by going directly to the place of business of the trainees. The conclusion of this dedication activity is that the students of Nusa Bhakti Vocational School are enthusiastic in accepting new knowledge and actively conducting questions and answers on how to motivate themselves and increase entrepreneurial insight in entering the workforce.Keywords: Motivation, Entrepreneurship, Vocational High School (SMK)